Math games & activities from around the world - Zaslavsky, Claudia (Chicago : Chicago Review Press, 1998)
Presents games and other activities from different countries and cultures that teach a variety of basic mathematical concepts.
"Multicultural fun for ages 9 & up"--Cover.
Includes bibliographical references (p. 144-145).
Young Adult
Keywords: Mathematical recreations -- Juvenile literature; Games; Mathematical recreations; Games; Mathematical recreations